Unified approach to robust control of robot manipulator using variable structure model-reaching control strategy - Yao, Bin (2009)
Robust control of mechanical manipulators in the presence of parametric uncertainties and external disturbances has been studied. Variable structure control (VSC) theory is adopted for the design of the controller method. Depending on the characteristics of the environment which the manipulator makes contact with, different control objectives can be achieved by a unified design approach method.